A regulatory protein-protein interaction governs glutamate biosynthesis in Bacillus subtilis: The glutamate dehydrogenase RocG moonlights in controlling the transcription factor GltC - Commichau, Fabian M.; Herzberg, Christina; Tripal, Philipp; Valerius, Oliver; Stülke, Jörg (Molecular Microbiology, 2007)
Glutamate synthesis is the link between carbon and nitrogen metabolism. In Bacillus subtilis, glutamate is exclusively synthesized by the glutamate synthase encoded by the gltAB operon. The glutamate dehydrogenase RocG from B. subtilis is exclusively devoted to glutamate degradation rather than to its synthesis. The expression of the gltAB operon is induced by glucose and ammonium and strongly repressed by arginine. Regulation by glucose and arginine depends on the transcriptional activator protein GltC. The gltAB operon is constitutively expressed in a rocG mutant strain, but the molecular mechanism of negative control of gltAB expression by RocG has so far remained unknown. We studied the role of RocG in the intracellular accumulation of GltC. Furthermore, we considered the possibility that RocG might act as a transcription factor and be able to inhibit the expression of gltAB either by binding to the mRNA or to the promoter region of the gltAB operon. Finally, we asked whether a direct binding of RocG to GltC could be responsible for the inhibition of GltC. The genetic and biochemical data presented here show that the glutamate dehydrogenase RocG is able to bind to and concomitantly inactivate the activator protein GltC. This regulatory mechanism by the bifunctional enzyme RocG allows the tight control of glutamate metabolism by the availability of carbon and nitrogen sources. © 2007 The Authors.
Created from Fastlane, Scopus look-up